Teaching computer programming to IPAD generation - Mahdin, Hairulnizam (2014)
Despites the advances in computer hardware and software, most of programming language introductory courses today still uses same old method to teach programming to the beginners. This made the acceptance towards the subject is quite slow and low where in most cases the concept only been grasped after the student had finished their study and started working. This paper presents available online modules that can be used to attract student interests towards the subject. There are many modules available that cover from basic programming up to the advanced apps development. We select three modules and conduct an introductory programming course to the primary school and diploma students. The result from the study shows that their perception about computer programming changed drastically when using these modules. They discover that computer programming is actually a fun and very interesting subject to be learned